HETEROGENEITY OF PROTEINS IN BIRDS’ EGG-WHITES - Hayder Obayes Hashim; Mohammed Baqur Sahib Al-Shuhaib; Mufeed Jaleel Ewadh (BIOTROPIA, 2019)
Little is known about the comparative heterogeneity of protein compounds among a wide variety of birds’ egg whites, particularly regarding detailed, parallel protein composition analysis. Therefore, this research was conducted mainly to evaluate the extent of variability among 42 types of birds’ egg whites. To improve the understanding of these biological fluids, the main phenotypic variations of egg whites were evaluated using discontinuous denaturing polyacrylamide gel electrophoresis (SDS-PAGE), gradient SDS-PAGE, native PAGE, cellulose acetate electrophoresis, and reverse-phase high-performance liquid chromatography (RP-HPLC). The results showed that native PAGE and SDS-PAGE produced better screening outcomes than the other methods in identifying proteins. Although native PAGE and SDS-PAGE did not show remarkable variability in terms of hydrophobicity, several electrophoretic differences in egg white proteins were observed. Several unknown proteins in the egg white samples of different bird species were also identified through electrophoretic experiments. Hence, it may be possible, as demonstrated in the case of egg white samples, to provide a characterization-based assessment among bird species using only available gel electrophoresis techniques. This study also provided a rapid snapshot for the initial identification of several unknown components of egg white proteins. Accordingly, this research represents the first large-scale comparative proteomics investigation conducted among a diverse range of egg whites obtained from commercial stores and bird keepers in the Middle Euphrates region of Iraq.